Effects of High Phosphorus Diet on Bone Metabolism-Related Gene Expression in Young and Aged Mice. (19th November 2014) - Katsumata, Shinichi; Matsuzaki, Hiroshi; Katsumata-Tsuboi, Rie; Uehara, Mariko; Suzuki, Kazuharu
Abstract : In this study, the effects of high phosphorus (P) diet on bone metabolism-related gene expression were investigated in young and aged mice. Twelve- and 80-week-old ddY male mice were divided into two groups, respectively, and fed a control diet containing 0.3% P or a high P diet containing 1.2% P. After 4 weeks of treatment, serum parathyroid hormone (PTH) concentration was significantly higher in the high P groups than in the control groups in both young and aged mice and was significantly higher in aged mice than in young mice fed the high P diet. High P diet significantly increased receptor activator of NF- κ B ligand (RANKL) mRNA in the femur of both young and aged mice and significantly increased the RANKL/osteoprotegerin (OPG) mRNA ratio only in aged mice. High P diet significantly increased mRNA expression of transient receptor potential vanilloid type 6, calbindin-D9k, and plasma membrane Ca 2+ -ATPase 1b in the duodenum of both young and aged mice. These results suggest that high P diet increased RANKL mRNA expression in the femur and calcium absorption-related gene expression in the duodenum regardless of age. Furthermore, the high P diet-induced increase in PTH secretion might increase the RANKL/OPG mRNA ratio in aged mice.